Emotionally Focused Couple Therapy with a Late-Life Couple: From Despair to Integrity - Skean, Karen Riggs; Brown, Elisabeth (Pragmatic Case Studies in Psychotherapy, 2024)
This commentary discusses the therapy of "Alice" and "Steve," a late-life married couple using Emotionally Focused Couple Therapy (EFCT) with a special emphasis on navigating Erik Erikson’s final psychosocial stage, that of Integrity vs. Despair. The support and validation offered the couple by a university-based student clinician allowed the couple to rewrite the narrative of their relationship in ways that helped them connect and be present for each other in a time of illness and impending loss. Implications for the benefits of teletherapy for expanding access are discussed.